Performance analyzes of a compact pico hydropower plant with a wide operating range - Pudji Irasari; Anwar Muqorobin; Puji Widiyanto; Tajuddin Nur; I Nengah Diasta; Priyono Soetikno (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
This paper analyzes the performance of a pico hydropower plant consisting of an axial hydro turbine integrated with a permanent magnet generator (PMG) and connected to a power converter. The proposed system is aimed to obtain a wide system operation range to gain more power captured while maintaining time-harmonic distortion in voltage (THDv) that meets the standard. The PMG specification is 1 kW, 1 phase, 235 V, 50 Hz, 83 rpm. The design and simulation of PMG were carried out by analytical and numerical calculations using FEMM 4.2. The power converter was simulated using PSIM and functions to reduce the THDv and pass the generator voltage between 50–500 V. The results show the THDv of the generating system at the upper and lower limits of the passed voltage having a THDv below 5%. Meanwhile, the PMG performance characteristics at various currents and rotations produce efficiency of 87.20% at nominal current. From these results, it can be concluded that the pico hydropower plant works well as desired.